SEKOLAH ISLAM TERPADU: REFORMASI BARU LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - Sukhoiri, Sukhoiri (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
The development of educational institutions in Indonesia is getting better day by day, this is also supported by various policies of the Indonesian government itself. The emergence of Islamic educational institutions with a full day school system is slowly but surely able to shift the public's interest in previous Islamic educational institutions such as Madrasah and Islamic Boarding Schools. Integrated Islamic schools with a full day school education system are administratively under the Ministry of Education and Culture, but the curriculum contents are dominated by religious lessons, the internalization of religious values in general lessons is the hallmark of the Integrated Islamic School. However, the presence of this educational institution is not without problems, because it is considered a high-cost school and is less affordable for people who are in the middle to lower economic class.ABSTRAKPerkembangan lembaga pendidikan di Indonesia semakin hari semakin membaik, hal ini juga didukung oleh berbagai kebijakan dari pemerintah Indonesia sendiri. Munculnya lembaga pendidikan Islam dengan sistem full day school secara perlahan namun pasti mampu menggeser minat masyarakat terhadap lembaga pendidikan Islam sebelumnya seperti Madrasah dan Pesantren. Sekolah Islam Terpadu dengan sistem pendidikan full day school secara administratif berada di bawah Kementrian Pendidikan dan Kebudayaan, namun muatan kurikulumnya didominasi oleh pelajaran agama, internalisasi nilai-nilai agama dalam pelajaran umum menjadi ciri khas Sekolah Islam Terpadu. Namun, kehadiran lembaga pendidikan ini bukan tanpa masalah, karena dianggap sebagai sekolah yang berbiaya tinggi dan kurang terjangkau oleh masyarakat yang berada di kelas ekonomi menengah ke bawah.